(untitled) (Jurnal Teknologi dan Informasi, 2020)
The use of Gadgets and Social Media at this time can not be separated from everyday life. This can lead to gadget and social media addiction. This study aims to answer whether the phenomenon of gadget addiction and social media is a scientific reality or not in Indonesia. Data was collected by a survei of 1601 respondents. Before the questionnaire was distributed, pearson product moment validity and reliability tests were performed with Cronbach’s alpha and the results showed that all questions on the questionnaire were valid and reliable. Based on the survei results, 42.45% of respondents experienced mild addiction, 10.82% of respondents experienced moderate level of addiction, and 0.38% of respondents experienced a very strong addiction to gadget. While the results for social media addiction, 37.50% of respondents experienced mild addiction, 7.85% of respondents experienced moderate level of addiction, and 0.38% of respondents experienced a very strong addiction to social media. In terms of the philosophy of science, Gadgets and Social Media Addiction is said to be science and not pseudo science because it has fulfilled the characteristics of science that is logical, empirical, and falsifiable. So it needs special attention from the community on the existence of gadget and media sosial addiction, so that this addiction can be anticipated and the symptoms can be minimized.